The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0090591
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of the Expression of Paralogous microRNA Precursors That Share the Same Major Mature Form

Abstract: BackgroundMicroRNAs (miRNAs) are a class of small non-coding RNAs generated from endogenous transcripts that form hairpin structures. The hairpin precursor is processed into two mature miRNAs that form major/minor duplexes. Mature miRNAs regulate gene expression by cleaving mRNA or repressing protein translation. Numerous miRNAs have been discovered via deep sequencing. Many miRNAs are produced from multiple genome sites. These miRNAs are grouped into paralogous families of miRNAs that generate the same major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Consistent with this study, we found that alcohol feeding increased serum exosomal miR192 but not miR194 levels (Figure 3C), further suggesting a local regulation of ileal miR194 by alcohol. We also found that the expression of both primary‐miR194‐2 ( pri‐miR194‐2 ) and primary‐miR194‐1 ( pri‐miR194‐1 ) in the ileum was increased by alcohol feeding, but the increase of pri‐miR194‐2 was more pronounced (Figure 3C), which is the major contributor to the expression of miR194 in the gastrointestinal tract 20. These results suggest partial transcriptional regulation of miR194 expression in the intestine by alcohol.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Consistent with this study, we found that alcohol feeding increased serum exosomal miR192 but not miR194 levels (Figure 3C), further suggesting a local regulation of ileal miR194 by alcohol. We also found that the expression of both primary‐miR194‐2 ( pri‐miR194‐2 ) and primary‐miR194‐1 ( pri‐miR194‐1 ) in the ileum was increased by alcohol feeding, but the increase of pri‐miR194‐2 was more pronounced (Figure 3C), which is the major contributor to the expression of miR194 in the gastrointestinal tract 20. These results suggest partial transcriptional regulation of miR194 expression in the intestine by alcohol.…”
Section: Resultsmentioning
confidence: 71%
“…We also found that the expression of both primary-miR194-2 (pri-miR194-2) and primary-miR194-1 (pri-miR194-1) in the ileum was increased by alcohol feeding, but the increase of pri-miR194-2 was more pronounced (Figure 3C), which is the major contributor to the expression of miR194 in the gastrointestinal tract. [20] These results suggest partial transcriptional regulation of miR194 expression in the intestine by alcohol. Interestingly, intestinal mucus-derived exosomes contain miR194, and it was significantly increased by alcohol feeding (Figure S5A).…”
Section: Alcohol Feeding Increased Ileal Mir194 Expressionmentioning
confidence: 87%
“…MicroRNAs (miRNAs) are endogenous small noncoding RNAs of 19~23 nucleotides (nt), which are diverse in sequence and expression patterns, suggesting that they may participate in a wide range of genetic regulatory pathways . They regulate gene expression through mRNA cleavage and translational repression by binding to the 3′ untranslated region of the target miRNA . To date, nearly 2700 miRNA genes have been identified in the human genome .…”
Section: Introductionmentioning
confidence: 99%